50 STEM labs : science, technology, engineering and mathematics - Frinkle, Andrew, ....- (S.l. : Andrew Frinkle, 2014)
This is a collection of 50 STEM (Science, Technology, Engineering, & Mathematics) science experiments for kids. Recommended for grades 3 and up. Each one has a snappy title, a brief description of the task required, the rules, and grading rubrics. These are very adjustable for your classroom, home, or homeschool needs. They support learning in these technical fields in a fun, hands-on, and sometimes competitive way. Learn by doing, measuring, and designing, and then reflect upon it. Labs are tagged with categories so you can search for other similar labs. Types of labs included are: paper airplanes, bridge building, roller coasters, weight lifting projects, cars, crash tests, egg tests, and many, many more!